The Contribution of Economic Research to Transport Policy Decisions: Introductory Reports and Summary of the Discussion (London: European Conference of Ministers of Transport (ECMT), [Washington, D.C.: sold by OECD Publications Center, 1977)
This research particularly demonstrates a picture of the transport system in the United Kingdom.
Includes bibliographies.
ne 27/02/2018
Loan
Keywords: Transportation; Economics; Transportation and State